Information organization in the radiophonic scenario of the universities of paraná from the recommendations of information architecture - De Paiva, Andréia Del Conte; Ficht, Nadia; Lunardelli, Rosane Suely Àlvares; Cervantes, Brígida Maria Nogueira [UNESP] (My University, 2018)
Based on assumptions of Information Science and Information Architecture, the central proposal of the study is to highlight the contributions of these areas of knowledge in the organization of sound information available on Paraná state public universities radio websites. Through documental, exploratory and descriptive research, with a qualitative-quantitative approach, the websites of four educational institutions were analyzed according to the items: if the interface of the site is user-friendly for occasional users; classification and intuitive research; connectivity to site information resources and external interfaces. The results of the study indicate that radio websites do not have the minimum organizational requirements necessary to efficiently and satisfactorily store and retrieve information. According to the panorama presented, it becomes evident the important role that the areas mentioned above play with regard to the process of information retrieval in the scope of university radio.
Organização da informação no cenário radiofonico de universidades paranaenses a partir das recomendações da arquitetura da informação
Keywords: Information Architecture; Information Organization; Information Science; University Radio